INOVASI KEPEMIMPINAN KEPALA MADRASAH DALAM MENGEMBANGKAN PROGRAM TAHFIDZUL QUR’AN DI MI NURUL ULUM BANTUL - Suci Muzfirah; Farida Noor Isnaini (ABDAU : Jurnal Pendidikan Madrasah Ibtidaiyah, 2025)
The headmaster is a leader as well as carrying out the task of achieving the goals of realizing the school's visions, as well as developing innovations that will be implemented in the daily life of the school. The strategic position of the principal has a great influence in realizing quality and quality education. At the MI level some of the things that distinguish from public schools are programs to their religion, one of which is Tahfidzul Qur'an. Tahfidzul Qur'an program is one of the achievements that are so important for graduates of MI Nurul Ulum, this is achieved seen from graduates who are competent at the mi level. This research aims to find out the innovation of madrasah head leadership in MI Nurul Ulum in developing tahfidzul Qur'an program as well as supporting factors and inhibitions. The research was conducted by researchers using qualitative methods with qualitative description approach. Data collection methods are conducted through structured interviews, observation and document analysis. While the data validity technique is using triangulation methods and data sources. Data analysis techniques using interactive models consist of data collection, data reduction, data presentation, and verification. The results showed the innovation of the leadership of the head of madrasah MI Nurul Ulum Bantul in expanding the Tahfidzul Qur'an program by applying yanbu'a method, carrying out exams per week, carrying out perjuz exam activities and rewarding students in the memorization process and in morality.